Integrative analysis reveals pathways associated with sex reversal in Cynoglossus semilaevis - Zhan Ye; Weifeng Wang; Yaqun Zhang; Liping Wang; Yu Cui; Hengde Li (PeerJ, 2020)
Sex reversal is a complex biological phenomenon exhibited by Cynoglossus semilaevis. Some genetic females may irreversibly convert to pseudomales, thus increasing aquaculture costs because males grow much more slowly than females. In this study, an integrative analysis of transcriptome and proteome was performed to compare differences in gene and protein expression in females and pseudomales after gonad differentiation in C. semilaevis. Based on RNA-Seq results, 1893 genes showed differences in expression at the transcript level between females and pseudomales. Of these differentially expressed genes (DEGs), zona pellucida sperm-binding protein 4-like (LOC103393374 , ZP4), zona pellucida sperm-binding protein 4-like (LOC103396071, ZP4) and forkhead box L2 (foxl2) were highly expressed in females and doublesex and mab-3 related transcription factor 1(dmrt1) and doublesex and mab-3 related transcription factor 3 (dmrt3) were highly expressed in pseudomales. GO enrichment analysis results indicate that wnt signaling pathways and oocyte maturation are two terms enriched in female. At the protein level, Tandem Mass Tags analysis revealed that 324 proteins differed in their relative abundance between pseudomales and females. KEGG analysis found that pseudo-highly expressed proteins were enriched in the ubiquitin mediated proteolysis pathway. For integrative analysis, the Spearman correlation coefficient between the transcriptome and proteome was 0.59. Among 52 related genes, 46 DEGs (88%) were well matched in their levels of change in protein abundance. These findings reveal major active pathways in female and pseudomale gonads after sex reversal and provide new insights into molecular mechanisms associated with sex reversal regulatory network.